Monitoring growth in asthmatic children treated with high dose inhaled glucocorticoids does not predict adrenal suppression. Issue 8 (21st July 2004) - Dunlop, K A; Carson, D J; Steen, H J; McGovern, V; McNaboe, J; Shields, M D
Abstract : Aims: To determine whether routine outpatient monitoring of growth predicts adrenal suppression in prepubertal children treated with high dose inhaled glucocorticoid. Methods: Observational study of 35 prepubertal children (aged 4–10 years) treated with at least 1000 μg/day of inhaled budesonide or equivalent potency glucocorticoid for at least six months. Main outcome measures were: changes in HtSDS over 6 and 12 month periods preceding adrenal function testing, and increment and peak cortisol after stimulation by low dose tetracosactrin test. Adrenal suppression was defined as a peak cortisol ⩽500 nmol/l. Results: The areas under the receiver operator characteristic curves for a decrease in HtSDS as a predictor of adrenal insufficiency 6 and 12 months prior to adrenal testing were 0.50 (SE 0.10) and 0.59 (SE 0.10). Prediction values of an HtSDS change of −0.5 for adrenal insufficiency at 12 months prior to testing were: sensitivity 13%, specificity 95%, and positive likelihood ratio of 2.4. Peak cortisol reached correlated poorly with change in HtSDS (ρ = 0.23, p = 0.19 at 6 months; ρ = 0.33, p = 0.06 at 12 months). Conclusions: Monitoring growth does not enable prediction of which children treated with high dose inhaled glucocorticoids are at risk of potentially serious adrenal suppression. Both growth and adrenal function should be monitored in patients on high dose inhaled glucocorticoids. Further research is required to determine the optimal frequency of monitoring adrenal function.